PERAN PELEMBAGAAN MASJID TUO DALAM PEMBENTUKAN KARAKTER MASYARAKAT SUMATERA BARAT (SEBUAH TINJAUAN TERHADAP SETTING SOSIAL DAN HISTORIS) - Muhammad Ridha; Eka Rizal; Nofri Andy.N; Zainal Zainal (Harmoni, 2022)
The existence of the masjid tuo in West Sumatera is not only known for its unique style and architecture with traditional and religious ties, but far behind that its institutional function gives rise to a distinctive character for the community. This article discusses how the masjid tuo plays a role in shaping the character of Minang society both structurally and culturally so that it becomes an important record for Minangkabau history (tambo). The method used in this study is descriptive qualitative in order to photograph the phenomena that develop in society related to the role of the masjid tuo so that social setting are known which include the existence of the masjid tuo. The result of this study indicates that the institutional role of masjid tuo in West Sumatera has shaped the character of minang community through the persona and functions that emerge from an imam, khatib, bilal, and labai. The role that is being carried out is an effort to produce syara’ regulation that will be carried out by children and nephews and the surrounding community of the nagari.